PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERINTEGRASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPS (JGuruku: Jurnal Penelitian Guru, 2023)
ABSTRACT This implementation of the problem based learning model, integrated differentiated learning, aims to increase the motivation of 7th grade social students in supply material. This study uses classroom action research. The data collection method used in this study is observation. It is to observe student and teacher activities. This method is also used to measure student learning outcomes. The students' average summative assessment results was 77. The students’ highest score was 90 and the lowest score was 60. Students experienced an increase in learning scores as seen from the lowest score data increased from cycle I. Thus, it can be concluded that the implementation of the problem based learning model, integrated differentiated learning of models in social studies subjects can increase student learning motivation